Strategi Pengabdian Masyarakat Melalui Kolaborasi Antar Mahasiswa (Studi Mahasiswa Penerima Beasiswa Yayasan Baitul Mal (YBM) PLN Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu) - Gustriani, Anisa; Dari, Tri Wulan; Farizal, Hengki; Cahyadi, Ashadi (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
This study aims to analyze, explain, and recount the strategies employed in collaborative activities among students receiving scholarships from the Baitul Mal Foundation (YBM) PLN at the State Islamic University (UIN) Fatmawati Sukarno Bengkulu. This study used a qualitative descriptive method, recounting the strategies employed in collaborative activities. The results of this study indicate that community empowerment strategies through collaboration among students receiving scholarships from the Baitul Mal Foundation (YBM) PLN at the State Islamic University (UIN) Fatmawati Sukarno Bengkulu, involve participating or collaborating in activities programmed by the Baitul Mal Foundation (YBM) PLN as a platform for students to gain experience.